SISTEM PERTANIAN LAHAN PEKARAGAN MENDUKUNG KETAHANAN PANGAN DAERAH SEMI-ARID: Kasus Kawasan Rumah Pangan Lestari di Provinsi Nusa Tenggara Timur - Yohanis Ngongo; Hendrik H Marawali (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2015)
ABSTRACTAgricultural System of Homegardening to Support Food Security in Semi-Arid Region: A Case Study of Sustainable Food Reserved Garden in East Nusa-Tenggara. The model of Sustainable Food Reserved Garden (SFRG) or m-KRPL has been developed in East Nusa Tenggara (ENT) since 2011 as a tool to empowering household in managing homeyard in order to, both improve household’s nutrition and income. This paper aimed to examine: 1) the diversity and specific characteristics of homeyards in ENT; and 2) the contribution of homeyard gardening to the beneficiaries of m-KRPL. Survey was conducted from October to December 2014. Six m-KRPL sites in three districts were chosen purposively based on main islands (Timor, Sumba, Flores) and agro-ecosystems (AEZ) representative (lowland and highland). The data was collected from Farm Record Keeping (FRK) and in-depth interviews using open-ended and semi-structure questionnaire. The data was analysed descriptively and also used farming analysis. The results showed that there are various types of homegarden practices among communities in the different AEZs. Homegarden practices confirm the similar goals for majority of farmers, that the produce plays role as a source of fresh and healthy food, as well as provides medicines, herbs and spices. Commodities planted in homegarden are more for subsistence; however, farmers who have an access to the market are willing to sell the excess production. Farming in homeyard could save household expenditure up-to Rp400,000/month. Existing plant species in the homegarden in Sikka district was higher than that in Sumba and TTS districts.  Nevertheless, for all districts, the horticultural plants was more diverse in highland than those in lowland.  Some identified constraints were water shortage, pest and diseases, free-range livestock, access to external inputs and market. Beside the technical-agronomic aspect, development of homegardening should consider homeyard as a “living space”, existing commodities, diet and market aspects. The implementation of m-KRPL should be extended to reach poor farmers.  Key words: Farming, homegarden, semi-arid area, subsistence.  ABSTRAKModel Kawasan Rumah Pangan Lestari (m-KRPL) telah dikembangkan di Provinsi Nusa Tenggara Timur (NTT) sejak tahun 2011 dalam rangka memberdayakan rumah tangga petani dalam mengelola pekarangan baik untuk memperbaiki kebutuhan gizi keluarga maupun untuk meningkatkan pendapatan. Makalah ini bertujuan untuk: 1) mengkaji keanekaragaman dan karakteristik spesifik pekarangan di NTT; dan 2) mengetahui kontribusi usahatani pekarangan terhadap rumah tangga petani peserta m-KRPL. Enam lokasi m-KRPL di tiga Kabupaten dipilih secara sengaja atas dasar keterwakilan pulau besar (Timor, Sumba dan Flores) dan zone-agroecosystem (ZAE dataran tinggi dan rendah). Survey dilaksanakan pada Oktober – Desember 2014. Data diperoleh dari pencatatan usahatani dan survey mendalam berpedoman pada kuesioner. Data dianalisis secara deskriptif dan juga menggunakan analisis usahatani. Hasil studi menunjukkan bahwa praktek pengelolaan pekarangan bervariasi antara berbagai kelompok masyarakat pada berbagai zone-agroecosystem yang berbeda, namun tetap mengkonfirmasi adanya kesamaan tujuan bagi dominan petani yakni sebagai sumber pangan yang sehat dan segar, penyedia obat-obatan herbal dan bumbu dapur. Komoditas yang diusahakan pada lahan pekarangan lebih untuk tujuan subsisten, namun sebagian petani yang mempunyai akses pasar yang baik menjual kelebihan produksi. Usahatani pekarangan dapat menghemat pengeluaran rumah tangga petani perserta program m-KRPL sampai Rp400.000/bulan. Jenis tanaman existing pada lahan pekarangan di Sikka lebih beragam jika dibandingkan dengan di lokasi pengkajian di Sumba Timur dan di TTS.  Untuk semua kabupaten lokasi kajian,  jenis tanaman hortikultura lebih banyak di dataran tinggi daripada di dataran rendah. Beberapa kendala yang dapat diidentifikasi adalah keterbatasan sumber air, hama dan penyakit, gangguan ternak, akses pada input luar dan pasar rendah. Disamping aspek teknis-agronomis, pengembangan usahatani pekarangan perlu memperhatikan pekarangan sebagai ruang hidup, komoditas existing, pola penghidupan, diet dan aspek pasar. Konsep m-KRPL perlu diperluas agar bisa menjangkau petani miskin sumberdaya. Kata kunci: Usahatani, pekarangan, daerah semi-arid, subsisten